(untitled) (Journal of Applied Learning and Teaching, 2023)
This paper addresses one of the pedagogical challenges that followed the presence of increasingly multinational student groups, particularly the increased diversity of academic backgrounds among students. Theoretically, this challenge can be understood as an encounter between different teaching and learning regimes (TLRs). TLR, coined by Trowler and Cooper (2002), implies a constellation of assumptions, rules, relationships, and practices regarding the conduct of higher education that colours academic staff members’ performance in their profession. It has become a widely used heuristic tool in the reflection process among university staff. It is shown in this paper that TLRs are not only a heuristic tool that can be applied in teacher reflection but may also be fruitfully applied in the classroom in student-teacher interaction. Consequently, we decided to bring the TLR into the classroom. The written student reflections constitute the empirical material that this analysis is based on. We approach these reflections as expressions of confessions of the Self, as laid out by Michel Foucault. We conclude that it is useful for the students to reflect upon TLR’s, but simultaneously, such an approach runs the risk of enhancing pedagogical and epistemological conformism at the neoliberal university.